Modeling Warehousing System to Improve Customer Responsiveness - Ilyas Masudin (Jurnal Gamma, 2009)
As a potential wide-separated island market, Indonesian logistics firms require a complex warehousing structure in distributing their products to entire part of areas. The problem raise when not all part of market areas receive the products with the same price and availability as the other places received. The product availability (customer responsiveness) in the multi echelon warehosing network depend on the optimum warehouse/distribution centre location determination Rosenfield and Pendrock (1986) have researched about the conflict between inventory level and customer service on the firms which practiced the centralized warehousing strategy. This research attempts to optimize the integrated strategies in implementing the warehousing policy, how to model the warehousing system effectively using the concept of warehousing location layout and the concept of centralized-distributed warehousing system with accommodating the probability of changes of the logistic elements like transportation-distribution, sales volume and the distance. The case study result shows that the optimum warehouse location should be located in the city of Pasuruan at the grid 514.2 horizontally and 143.8 vertically. From that case, the firm automatically could deliver the products in the huge scale to gain the unit cost reduction (economic sacle) which finally could raise the customer responsiveness (product avaliability). The sensitivity analysis also shows that the distance (from source to market) of determined warehouse location affect the transport rate.